Quadratic Equation: Sum and Product of Roots

13,789

Quadratic Equation: Sum and Product of Roots:

A general quadratic equation is given by

ax2 + bx + c = 0
, where
a,b
and
c
are constants with
a  0
. The solutions or the roots of the above quadratic equation can be given by quadratic formula as :

x = b ± b2  4ac2a

 x = b2a ± b2  4ac2a

The term

b2  4ac
is the discriminant of the equation
ax2 + bx + c = 0
and is denoted by D or Δ.

 x = b2a ± D2a

If the roots of this equation are given by

α
and
β
, then there exists a relationship between the roots of quadratic equation and the coefficients
a,b
and
c
. The relationship is given as:

α + β = ba

αβ = ca

Sum of Roots

Thus, the sum of roots of a quadratic equation is given by the negative ratio of coefficient of

x
and
x2
. The product of roots is given by ratio of the constant term and the coefficient of
x2
.

Let us try to prove this graphically.

We know that the graph of a quadratic function is represented using a parabola. If α and β are the real roots of a quadratic equation, then the point of intersection of the plot of this function with x-axis represents its roots.

Let us assume that

D2a = n
. Roots can be also given as

α = b2an
—(1)

β = b2a+n
—(2)

Graphically, it can be shown as:

Sum and product of roots

Adding equations (1) and (2), we get

α + β = 2b2a

α + β = ba

Also,

α = b  b2  4ac2a

β = b + b2  4ac2a

Multiplying both these equations we get

αβ = b  b2  4ac2a × b + b2  4ac2a

 αβ =(b)2  (b2  4ac)4a2

αβ = ca

Consider the general form of quadratic equation

ax2 + bx + c = 0
.

Dividing both sides by

a
, we get,

aa x2 + ba x + ca = 0

 x2 + ba x +ca = 0

Since,

α + β = ba

αβ = ca

 x2  (α + β) x + αβ = 0

Thus by using roots, the equation can be obtained.

Consider the following two equations:

x2 + 2x  3 = 0
and
2x2 + 4x  6 = 0
.

The roots of these equations are equal i.e. 1 and -3. Graphically, these equations intersect thex-axis at the same points as shown below.

Sum and product of roots

If the coefficients of two quadratic equations having same roots is given by

a1,b1,c1
and
a2,b2,c2
. Then, the following relation holds true

a1b1 = a2b2 = c1c2

The relationship between roots and coefficients of an equation can be established for higher order equations too. We know that the degree specifies how many roots an equation can have. The number of roots of an equation is equal to its degree. Let us take an

nth
order function and see how roots and coefficients are related to each other.

For a function

f(x) = anxn + an1 xn1 +..+ a1x + a0
, if the roots are given by
αn1,αn2α0
,

then,

f(x) = αn(x  αn1)(xαn2)(xα0)

anxn + an1xn1 +.. + a1x + a0 = αn(x  αn1)(x  αn2)(xα0)

On comparing coefficients of

xn1
,we get:

S1 = αn1 + αn2 +  + α0 = i=0n1αi = an1an = (1)1
coefficient of xn1coefficient of xn

On comparing coefficients of

xn2
, we get:

S2 = (αn1)(αn2) + (αn2)(αn3) +  = i  jαiαj = an2an = (1)2coefficient of xn2coefficient of xn

On comparing coefficients of

xn3
, we get:

S2 = (αn1)(αn2)(αn3) + (αn2)(αn3)(αn4) +  = ijkαiαjαk

=

an3an = (1)3 coefficient of xn3coefficient of xn

Similarly,

Sn = (αn1)(αn2)(αn3)  α0 = (1)n a0an = (1)n constant termcoefficient of xn

Thus, for a quadratic equation of the form

ax2 + bx + c = 0
, having roots
α
and
β
,

α + β = ba

αβ = ca

For cubic equation of the form

ax3 + bx2 + cx + d = 0
, having roots α,β and γ,

α + β + γ = ba

αβ + βγ + γα = ca

αβγ = da

For a fourth degree equation known as quartic equation in general form is given by:

ax4 + bx3 + cx2 + dx + e = 0

If its roots are

α,β,γ
and
δ
then

α + β + γ + δ = ba

αβ + αγ + αδ + βγ + γδ + δβ = ca

αβγ + βγδ + γδα + αβδ = da

αβγδ = ea

Thus, this process can be continued to find out the relationship between the roots and the coefficients of any equation of

nth
degree. Thus, sum and product of roots can be found out easily.’

Comments

Leave a Comment

Your Mobile number and Email id will not be published.

*

*